Characteristics and Outcomes of Recipients of Heart Transplant With Coronavirus Disease 2019 - Latif, Farhana (JAMA Cardiol, 2020)
IMPORTANCE: Recipients of heart transplant (HT) may be at increased risk of adverse outcomes attributable to infection with coronavirus disease 2019 (COVID-19) because of multiple comorbidities and clinically significant immunosuppression. OBJECTIVE: To describe the characteristics, treatment, and outcomes of recipients of HT with COVID-19. DESIGN, SETTING, AND PARTICIPANTS: This case series from a single large academic heart transplant program in New York, New York, incorporates data from between March 1, 2020, and April 24, 2020. All recipients of HT followed up by this center who were infected with COVID-19 were included. INTERVENTIONS: Heart transplant and a confirmed diagnosis of COVID-19. MAIN OUTCOMES AND MEASURES: The primary measure was vital status at end of study follow-up. Secondary measures included patient characteristics, laboratory analyses, changes to immunosuppression, and treatment administered for COVID-19. RESULTS: Twenty-eight patients with HT received a confirmed diagnosis of COVID-19. The median age was 64.0 (interquartile range [IQR], 53.5-70.5) years, 22 (79%) were men, and the median time from HT was 8.6 (IQR, 4.2-14.5) years. Comorbid conditions included hypertension in 20 patients (71%), diabetes in 17 patients (61%), and cardiac allograft vasculopathy in 16 patients (57%). Twenty-two participants (79%) were admitted for treatment, and 7 (25%) required mechanical ventilation. Most (13 of 17 [76%]) had evidence of myocardial injury (median high-sensitivity troponin T, 0.055 [IQR, 0.0205-0.1345] ng/mL) and elevated inflammatory biomarkers (median peak high-sensitivity C-reactive protein, 11.83 [IQR, 7.44-19.26] mg/dL; median peak interleukin 6, 105 [IQR, 38-296] pg/mL). Among patients managed at the study institution, mycophenolate mofetil was discontinued in 16 patients (70%), and 6 (26%) had a reduction in the dose of their calcineurin inhibitor. Treatment of COVID-19 included hydroxychloroquine (18 patients [78%]), high-dose corticosteroids (8 patients [47%]), and interleukin 6 receptor antagonists (6 patients [26%]). Overall, 7 patients (25%) died. Among 22 patients (79%) who were admitted, 11 (50%) were discharged home, 4 (18%) remain hospitalized at the end of the study, and 7 (32%) died during hospitalization. CONCLUSIONS AND RELEVANCE: In this single-center case series, COVID-19 infection was associated with a case fatality rate of 25% in recipients of HT. Immunosuppression was reduced in most of this group of patients. Further study is required to evaluate the optimal approach to management of COVID-19 infection in the HT population.